Three new species of Pergalumna (Acari: Oribatida: Galumnidae) from the tropical rainforest of Veracruz, Mexico - Palacios-Vargas, José G.; Villagomez, Fernando (Zootaxa, 2017)
Three new species of oribatid mites of the genus Pergalumna from a tropical rain forest in Veracruz, Mexico are described. Pergalumna hypergranulosa sp. nov. differs from Pergalumna granulatus Balogh & Mahunka, 1967 by unilaterally barbulated bothridial setae, elongated notogastric porose areas, and also a more profuse granulation of the cerotegument. Pergalumna obsidiana sp. nov. differs from P. granulatus by the unilateral barbulation of bothridial setae and the presence of protuberances on the genital plates; from Pergalumna paralongisetosa Ermilov & Kalúz, 2012 by a diverging cerotegumental granulation on the notogaster. Pergalumna dactylaris sp. nov. differs from Pergalumna striata (Pérez-Íñigo & Baggio, 1980) by its bigger size and the presence of three notogastric porose areas instead of four and from Pergalumna decorata Balogh & Mahunka, 1977, also by the bigger size, a different position of setae lm and la and smaller but not minute interlamellar setae. These are the first Mexican species descriptions of this genus.